Compound 15c, a Novel Dual Inhibitor of EGFRL858R/T790M and FGFR1, Efficiently Overcomes Epidermal Growth Factor Receptor-Tyrosine Kinase Inhibitor Resistance of Non-Small-Cell Lung Cancers - Chen, Gaozhi; Bao, Yuyan; Weng, Qiaoyou; Zhao, Yingxin; Lu, Xiaoyao; Fu, Lili; Chen, Lingfeng; Liu, Zhiguo; Zhang, Xiaomin; Liang, Guang (Frontiers in Pharmacology, 2020)
In the past decades, epidermal growth factor receptor-tyrosine kinase inhibitors (EGFR-TKIs) had been proved as an effective treatment strategy for the patients with EGFR-mutated non-small-cell lung cancer (NSCLC). However, the tolerance for the EGFR-TKI always occurred after continuous administration for a period of time and limiting the application of these drugs. Activation of FGFR1 signaling pathway was one of the important escape mechanism for EGFR-TKI resistant in NSCLC. Here, a novel dual inhibitor of EGFRL858R/T790M and FGFR1, compound15c, was found and can efficiently overcame the EGFR-TKI resistance via its simultaneous inhibition of their kinase activities. Comparison with EGFRL858R/T790M and FGFR1 inhibitor treatment alone or combined revealed that the inhibition of EGFRL858R/T790M and FGFR1 activity by 15c was responsible for surmounting the intrinsic EGFR-TKI resistance in EGFRL858R/T790M-mutated H1975 cells and the acquired resistance in Afatinib-tolerant PC9 cells (AFA-PC9). Flow Cytometry and Caspase3 activity analysis assay showed that 15c induced significant the early apoptosis of H1975 cells. Xenograft tumor formation in BALB/c mice induced by a H1975 cells was suppressed by 15c treatment, with no changes in animal body weight. Generally, 15c may act as a new-generation EGFR-TKI for the therapy of NSCLC patients suffering a resistance to current TKI.